Diversity of properties of sawmill residues used as feedstock for energy generation. (January 2023) - Dudziec, Paweł; Stachowicz, Paweł; Stolarski, Mariusz J.
Abstract: Sawmill residues are used in the power industry, where it accounts for the greatest portion of solid biomass used in combined heat and power plants and heat-generating plants, mainly as chips. This results in increasing demand for this material around the world, which makes the characteristics and variability of sawmill biofuels increasingly important. The objective of this study was to determine the energy-related properties of Pinus sylvestris L. residues depending on the tree growth site (five locations), date of harvest (autumn, winter) and the type of biomass (sawdust, wood slabs). These three factors were found to significantly diversify a large majority of the sawmill residue properties. Sawmill residues had higher LHV compared to the level generally determined for wood (of similar moisture content), and the type of sawmill residue explained to the greatest extent the variability of the largest number of attributes. Wood slabs generally had worse properties than sawdust, and the differences between the forest districts were identical with the influence of the location. In the case of the harvest date, it was found that the source of variability was in fact, inter alia, "nested" in the season of the relative air humidity. Graphical abstract: Image 1